NMR and computational studies reveal novel aspects in molecular recognition of unsaturated fatty acids with non‐labelled serum albumin. (16th April 2022) - Alexandri, Eleni; Primikyri, Alexandra; Papamokos, Georgios; Venianakis, Themistoklis; Gkalpinos, Vasileios K.; Tzakos, Andreas G.; Karydis‐Messinis, Andreas; Moschovas, Dimitrios; Avgeropoulos, Apostolos; Gerothanassis, Ioannis P.
Abstract : An approach based on the combined use of saturation transfer difference (STD), Tr‐NOESY and Inter‐ligand NOEs for PHArmacophore Mapping (INPHARMA) NMR techniques and docking calculations is reported, for the first time, for mapping interactions and specific binding sites of caproleic acid (10 : 1 cis‐9), oleic acid (18 : 1 cis‐9), linoleic acid (18 : 2 cis‐9, 12) and linolenic (18 : 3, cis‐9, 12, 15) free fatty acids (FFAs) with non‐labelled serum albumin (BSA/HSA). Significant negative inter‐ligand NOEs between the FFAs and the drugs ibuprofen and warfarin, through competition experiments, were observed. The inter‐ligand NOEs and docking calculations were interpreted in terms of competitive binding mode, the significant folding of the bis allylic region and the presence of two orientations of the FFAs in the warfarin binding site (FA7), due to two potential distinctive anchoring polar groups of amino acids. This conformational flexibility is the reason that, the location and conformational states of the FFAs in the binding site of warfarin could not be determined accurately, despite numerous available X‐ray structural studies. α‐Linolenic acid competes favourably with warfarin at the binding site FA7. Isothermal titration calorimetry experiments of the preformed HSA/α‐linolenic acid complex upon titration with warfarin show a significant reduction in the binding constant of warfarin, in very good agreement with NMR and computational data. The combined use, therefore, of STD, Tr‐NOESY and INPHARMA NMR, ITC and docking calculations may find promising applications in the field of protein–lipid recognition research. Abstract : The study reports inter‐ligand 2D NMR NOEs and docking calculations of the interaction of unsaturated free fatty acids (FFAs) with serum albumin. The results demonstrate two orientations of the FFAs in the warfarin binding site (FA7), due to two anchoring groups of polar amino acids. This conformational flexibility is the reason that the position of the FFAs in FA7 could not be determined accurately in X‐ray structural studies.